Fingerprint Based Gender Classification Using Discrete Wavelet Transform And K-Nearest Neighbor - Abdullah, Siti Fairuz; Abdul Rahman, Ahmad Fadzli Nizam; Mahadhir, Majidah; Abal Abas, Zuraida (IJCSIS, 2016)
-